THE ROLE AND EXISTENCE OF HERBAL MEDICINE IN TRADITIONAL MEDICINE INDONESIA - Gunawan Widjaja (Jurnal Kesehatan, 2024)
This study aims to systematically review the literature related to the application and impact of herbal medicine in traditional and contemporary medicine in Indonesia. The research method used was a literature study, where data was collected through a systematic search of articles, journals, and scientific publications related to the use of herbal medicine. The results of the literature review showed that jamu has significant potential as an alternative and complementary medicine, especially in the treatment of diverse health conditions such as diabetes, hypertension, and other chronic diseases. Studies highlighted the importance of the diverse chemical composition of herbs, including active compounds such as flavonoids, alkaloids and terpenoids, which contribute to their therapeutic effects. However, the study also underscores the importance of further research regarding standardization, effective dosing, and assessment of potential risks of jamu use to ensure safety and efficacy for users